Comparison between von Willebrand Factor (VWF) and VWF Antigen II in Normal Individuals and Patients with von Willebrand Disease - Romeuf, Christophe de; Mazurier, Claudine (Thrombosis and Haemostasis, 1998)
Von Willebrand disease is characterised by a quantitative (type 1) or qualitative (type 2) decrease in von Willebrand factor (vWF) a multimeric glycoprotein involved in primary haemostasis. The propep-tide of von Willebrand, also named vWF antigen II (vWF:AgII), is released from platelets and endothelial cells and circulates in plasma as a glycoprotein of 100 kD. In the present study, we attempted to determine whether vWF:AgII level may provide information on the synthesis of vWF, specially in patients with von Willebrand disease (vWD). To elucidate that point, we developed an ELISA and quantify the vWF:AgII in normal individuals and in various vWD patients. The propeptide molar concentration was found to be 5nM as compared to 31 nM for mature vWF. In normal individuals, the level of vWF:AgII was significantly decreased in females from O and A blood groups. In type 2 vWD patients the level of plasma vWF:AgII appears normal in the patients with normal level of platelet vWF. In type 2 B vWD characterised by increased affinity of mature vWF for platelet glyco-protein Ib, the vWF:Ag II in contrast to the vWF antigen (vWF:Ag) was not decreased. In type 2A vWD patients the level of vWF:AgII was decreased in patients with absence of high molecular weight vWF in platelets and plasma but normal in patients with increased sensitivity to proteolysis. Finally, in type 1 vWD, some studied patients have a parallel decrease in vWF:AgII and vWF:Ag whereas in others, the vWF:Ag levels were much more affected than corresponding vWF:AgII levels, as observed in some type 2 vWD patients. Thus, in contrast to that already described, the plasma vWF:AgII level cannot discriminate type 1 from type 2 vWD patients. We conclude that the vWF:AgII measurement provides additional information on the mechanisms responsible for vWD and might also contribute to the classification of vWD patients.